Graduate Students Perceptions' on Multicultural Education: A Qualitative Case Study - Aydin, Hasan; Tonbuloglu, Betul (ANI YAYINCILIK, 2014)
Problem statement: The main responsibility in the implementation of multicultural education, which includes notions like equality, respect, and peace, as well as an equal opportunity for success for all students, belongs to teachers. The teachers. perception of and attitude towards multicultural education are directly related to how they will implement multicultural education. Some past studies indicate that there is an undeniable effect of culture on education, yet teaching candidates and managers often don't have sufficient knowledge of multicultural education. Data gathered from this study is expected to contribute to the literature on multicultural education practices expected to be included in Turkey's educational programs. Purpose of Study: The purpose of this study is to find out the perception of and the evaluation of multicultural education by participants who work as primary and secondary education teachers who are continuing their doctorate level education in curriculum and instruction. Method: In this inquiry, a qualitative case study approach was used. It has been carried out in the setting of a doctorate level multicultural education class at one of largest state university in Turkey's Educational Science Department. The participants in this study consisted of nine doctorate students taking this course in the Spring of the 2013 academic year, five of which were teachers and four were academicians. Data was collected based on informal interviews, observations, field-notes, and document analysis. A weekly discussion board of reflections, examination papers, and observation forms were also used for more objective results. Gathered data was evaluated through the content analysis technique and the results are presented as a report. Findings and Results: The findings of this study indicate that equality, democracy, and justice are the most emphasized notions and it has been stated that multicultural education will reinforce these notions. In addition to this, all participants stressed the necessity of taking individual differences into account and expressed that this is cultural richness. Tolerance, respect, and peace are also some of the most commonly mentioned notions. Conclusions and Recommendations: The need for people with different characteristics and cultures to live with equal rights and every group of the society to have an equal and democratic structure make multicultural education a necessity. Even though the number of studies on multicultural education conducted in Turkey is limited, we recommend that more studies should be conducted like they are in countries with more advanced democracies and that the educational programs should be extended to include multicultural education.
Keywords: multicultural education; equality; democracy; justice; and qualitative research; Education & Educational Research